Penguatan Kurikulum Indonesia Melalui Integrasi Praktik Computational Thinking pada Kurikulum Nasional Inggris - Azizia, Ananda Jullailatul; Waluya, St. Budi; Mulyono, Mulyono (Papanda, 2026)
The rapid development of digital technology demands that education systems prepare students with higher-order thinking skills and digital literacy. Computational Thinking (CT) has become one of the key competencies of the 21st century, emphasizing the ability to decompose problems, recognize patterns, apply abstraction, and design algorithms for effective problem-solving. This article aims to analyze the integration of CT practices within the National Curriculum of England and its relevance to strengthening Indonesia’s Merdeka Curriculum. The research method used is a literature study with a comparative analysis of educational policy documents, international research findings, and models of CT implementation in England. The study reveals that England has successfully positioned CT as a core competency through the Computing subject introduced in 2014, supported by a systematic, progressive, and tiered curriculum structure. The implementation of CT in England encompasses three main domains Computer Science, Information Technology, and Digital Literacy and emphasizes project-based and reflective pedagogical approaches. The successful integration of CT is supported by a clear curriculum framework, teacher readiness, and the development of contextual learning resources.The relevance for Indonesia lies in the alignment between CT principles and the direction of the Merdeka Curriculum, which emphasizes Higher Order Thinking Skills (HOTS), creativity, and digital literacy. Adapting the English approach can be achieved through three key strategies: developing tiered CT competency standards, implementing project-based teacher training, and providing contextual learning materials suited to local conditions. The systematic integration of CT has the potential to strengthen the Profil Pelajar Pancasila (Pancasila Student Profile), enhance national digital literacy, and realize an adaptive, innovative, and globally competitive Indonesian education system